Odpowiedzi

Najlepsza Odpowiedź!
2010-02-25T19:28:18+01:00
A) x + 5 =10
x= 10-5
x=5
b) 2x + 3 =15
2x=15-3
x=6
c) 5x + 13 =23
5x= 23-13
x=2
d) 3x + 11 =41
3x=41-11
x=10
e) -x + 2 =8
-x=8-2
x=-6
f) -x + 5 =-2
-x=-2-5
x=7
g) -2x - 7 =11
-2x=11+7
x=-9
h) -5x + 3= -12
-5x=-12-3
x=3
i) -1,5x + 2 = 9,5
-1,5x=9,5-2
x=-5
2 4 2
2010-02-25T19:30:41+01:00
A) x=10-5 x=5
b)2x=15-3 2x=12 x=6
c) 5x + 13 =23 5x=23-13 5x=10 x=2
d) 3x + 11 =41 3x=30 x=10
e) -x + 2 =8 -x=6 x=-6
f) -x + 5 =-2 -x=-7 x=7
g) -2x - 7 =11 -2x=11+7 -2x=18 x=-9
h) -5x + 3= -12 -5x=-15 x=5
i) -1,5x + 2 = 9,5 -1.5x=7,5/(1,5) x=-5
1 1 1